2015
DOI: 10.2474/trol.10.420
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Mechanism of Humidity to Influence the Very Early Stage of Sliding under Different Load

Abstract: A study was carried out on the influences of atmospheric humidity in the very early stage of sliding for austenitic stainless steel (JIS SUS316). Pin-on-disk tests were conducted under different rates of relative humidity (RH). A relatively low magnitude of applied load to lessen the influences of mechanical effect was employed for emphasizing the humidity effect on tribological phenomena. The results of the current study were compared with our previous study results obtained at higher magnitude of applied loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…A ball-toball scratching test of austenitic stainless steel shows a singular phenomenon that the lateral force observed at a downhill motion shows extraordinarily high value compared with that at an uphill motion especially in the atmospheric air with medium RH [14]. The detection of the singular phenomenon at medium RH corresponds with the findings of both the shortest ISP [13,14] and the highest wear rate [1,2] at medium RH in previous studies on metallic materials. The correspondence suggests that the further understanding of the singular phenomenon may play an important role to reveal the dominant mechanisms of RH to influence sliding phenomena.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…A ball-toball scratching test of austenitic stainless steel shows a singular phenomenon that the lateral force observed at a downhill motion shows extraordinarily high value compared with that at an uphill motion especially in the atmospheric air with medium RH [14]. The detection of the singular phenomenon at medium RH corresponds with the findings of both the shortest ISP [13,14] and the highest wear rate [1,2] at medium RH in previous studies on metallic materials. The correspondence suggests that the further understanding of the singular phenomenon may play an important role to reveal the dominant mechanisms of RH to influence sliding phenomena.…”
Section: Introductionsupporting
confidence: 67%
“…The amount of adsorbed water increases with the increase in the surface roughness of the sample [11]. In the very early stage of the sliding of self-mated austenitic stainless steel shows an initial steady period (ISP) which does not show micron-level or larger adhesion phenomena and the length of ISP is shorter at medium RH than those at low or high RH [12,13]. A ball-toball scratching test of austenitic stainless steel shows a singular phenomenon that the lateral force observed at a downhill motion shows extraordinarily high value compared with that at an uphill motion especially in the atmospheric air with medium RH [14].…”
Section: Introductionmentioning
confidence: 99%
“…The research group by the current authors aimed to obtain quantitative data on the effect of RH and the adsorbed water layer in sliding phenomena. They initially focused on investigating the early stages of sliding in metallic materials using a pin-on-disc setup to simplify the analysis [15][16][17][18]. For example, when studying the sliding of SUS 316, it was observed that at a moderate RH of 49%, severe adhesion occurred earlier compared to low and high RH [15].…”
Section: Introductionmentioning
confidence: 99%
“…Wei Chee Hong 1) , Kanao Fukuda 1, 2) * and Shahira Liza 1) By employing similar experimental conditions with varying applied loads, the authors discovered that severe adhesion starts earliest when a low applied load is combined with high RH [17]. The adsorbed water at different RH levels and applied loads exhibited different mechanisms that influenced friction and wear of materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation